The efficacy of immunoglobulin replacement therapy in the long-term follow-up of the B-cell deficiencies (XLA, HIM, CVID) - Bayrakci, Benan; Ersoy, Fügen; Sanal, Ozden; Kiliç, Sebnem; Metin, Ayşe; Tezcan, Ilhan (The Turkish Journal of Pediatrics, 2005)
Immunoglobulin replacement therapy is the essential treatment of B-cell deficiencies. Because of the high expense of therapy, optimal dose, infusion intervals and serum IgG levels should be well defined. Data of 19 X-linked agammaglobulinemia (XLA), 7 hyper-IgM syndrome (HIM) and 20 common variable immunodeficiency (CVID) patients were analyzed. Infection frequencies and hospitalization requirements were correlated with the immunoglobulin doses used and serum IgG levels achieved. The characteristics before diagnosis and after treatment were compared among the XLA, HIM and CVID groups. By using a median dose of 370 mg/kg/month immunoglobulin, which maintained serum IgG levels at a median concentration of 440 mg/dl, the annual incidence of infections dropped from 12.4 to 3.2 and annual hospitalization requirements decreased from 1.6 to 0.16 per patient. Serum IgG levels of 300-500 mg/dl were found to be satisfactory, except in the CVID group. Increasing the level over 500 mg/dl neither prevented pneumonia further nor decreased the need for hospitalization. Monthly replacement was found to be adequate, except for XLA patients. Serum IgG levels between 300-500 mg/dl are sufficient for effective treatment of hypogammaglobulinemias. These concentrations can be maintained with 300-400 mg/kg/month doses. Higher doses and IgG levels are not needed.